Analysis of the loading properties of fowl eggshell with finite element method - SONG Hui-zhi; WANG Jun; YE Jun-an (浙江大学学报. 农业与生命科学版)
The research on the loading behaviour of fowl egg was carried out using finite element simulation. The reliability of simulation numerical solutions was verified through comparing the experimental outcome. The stress distribution and displacement of eggshell were analyzed under different conditions of force or pressure. The correlation between the loading properties and geometrical characteristics of the egg was investigated by using a numerical model analysis. The results showed that the strength and displacement of the lateral side of the egg was greater than the ogival nose. The stress increased as the egg's thickness increased, and there was no obvious correlation between the loading properties of eggshell and the ogival factor.